Homeostatic Control of the Thyroid–Pituitary Axis: Perspectives for Diagnosis and Treatment - Hoermann, Rudolf; Midgley, John E. M.; Larisch, Rolf; Dietrich, Johannes W. (Frontiers in Endocrinology, 2015)
The long-held concept of a proportional negative feedback control between the thyroid and pituitary gland requires reconsideration in the light of more recent studies. Homeostatic equilibria depend on dynamic interrelationships between thyroid hormones and pituitary thyrotropin (TSH). They display a high degree of individuality, thyroid-state-related hierarchy and adaptive conditionality. Molecular mechanisms involve multiple feedback loops on several levels of organization, different time scales and varying conditions of their optimum operation, including a proposed feedforward motif. This supports the concept of a dampened response and multistep regulation, making the interactions between TSH, FT4 and FT3 situational and mathematically more complex. As a homeostatically integrated parameter, TSH becomes neither normatively fixed nor a precise marker of euthyroidism. This is exemplified by the therapeutic situation with L-thyroxine (L-T4) where TSH levels defined for optimum health may not apply equivalently during treatment. In particular, an FT3-FT4 dissociation, discernible FT3-TSH disjoint and conversion inefficiency have been recognised in L-T4-treated athyreotic patients. In addition to regulating T4 production, TSH appears to play an essential role in maintaining T3 homeostasis by directly controlling deiodinase activity. While still allowing for tissue-specific variation this questions the currently assumed independence of the local T3 supply. Rather it integrates peripheral and central elements into an overarching control system. On L-T4 treatment, altered equilibria have been shown to give rise to lower circulating FT3 concentrations in the presence of normal serum TSH. While data on T3 in tissues are largely lacking in humans, rodent models suggest that the disequilibria may reflect widespread T3 deficiencies at the tissue level in various organs. As a consequence, the use of TSH, valuable though it is in many situations, should be scaled back to a supporting role that is more representative of its conditional interplay with peripheral thyroid hormones. This reopens the debate on measurement of free thyroid hormones and encourages the identification of suitable biomarkers. Homeostatic principles conjoin all thyroid parameters into an adaptive context, demanding a more flexible interpretation in the accurate diagnosis and treatment of thyroid dysfunction.